2014
DOI: 10.1371/journal.pone.0116064
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Human Patient-Derived Endometrial Cancer Xenografts in NOD scid Gamma Mice for the Study of Invasion and Metastasis

Abstract: ObjectiveMost endometrial cancers are detected early and have a good prognosis, while some endometrial cancers are highly invasive, metastasize early, and respond suboptimally to therapy. Currently, appropriate model systems to study the aggressive nature of these tumors are lacking. The objective of this study was to establish a mouse xenograft model of endometrial tumors derived from patients in order to study the biological aggressive characteristics that underlie invasion and metastasis.MethodsEndometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Endometrioid TOV112D ovarian cancer cell line was cultured in a 1:1 mixture of MCDB 105 medium and Medium 199, supplemented with 15% HI-FBS. Patient-derived primary endometrioid endometrial cancer xenograft (PDX) EEC-4 was a gift from J.J.Kim’s laboratory and maintained in RPMI 1640 with 10% HI-FBS ( Unno et al, 2014 ). Cisplatin-resistant primary endometrial cancer cell line HEC1a was cultured in modified McCoy’s 5a medium.…”
Section: Methodsmentioning
confidence: 99%
“…Endometrioid TOV112D ovarian cancer cell line was cultured in a 1:1 mixture of MCDB 105 medium and Medium 199, supplemented with 15% HI-FBS. Patient-derived primary endometrioid endometrial cancer xenograft (PDX) EEC-4 was a gift from J.J.Kim’s laboratory and maintained in RPMI 1640 with 10% HI-FBS ( Unno et al, 2014 ). Cisplatin-resistant primary endometrial cancer cell line HEC1a was cultured in modified McCoy’s 5a medium.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Unno et al [ 34 ] established a xenograft model by transplanting fragments of four different EC histologies, from patients undergoing surgery, into the renal capsule of NSG mice. Following this approach, the authors reported that tumour xenografts retain characteristics of the original tumour and display features that are unique to endometrioid EC or non-endometrioid EC.…”
Section: Endometrial Cancer Pdx Modelsmentioning
confidence: 99%
“…Following this approach, the authors reported that tumour xenografts retain characteristics of the original tumour and display features that are unique to endometrioid EC or non-endometrioid EC. In addition, they showed that each model has a different invasive and metastatic capacity according to its histology as well as a distinct dependence on β-estradiol [ 34 ]. Despite the technical difficulties presented by this type of approach, a renal capsule xenograft model is suitable for studying aggressive EC since tumour cells are in an environment susceptible to invasion and metastasis.…”
Section: Endometrial Cancer Pdx Modelsmentioning
confidence: 99%
“…Endometrioid TOV112D ovarian cancer cell line was cultured in a 1:1 mixture of MCDB 105 medium and Medium 199, supplemented with 15% HI-FBS. Patientderived primary endometrioid endometrial cancer xenograft (PDX) EEC-4 was a kind gift from Dr. Kim's laboratory and maintained in RPMI 1640 with 10% HI-FBS (Unno K, 2014). Cisplatin-resistant primary endometrial cancer cell line HEC1a was cultured in modified McCoy's 5a medium.…”
Section: Cell Culturementioning
confidence: 99%